2014
DOI: 10.4103/0971-6580.155336
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mycotoxin exposure in CÔte D′ivoire (Ivory Coast) through multi-biomarker analysis and possible correlation with food consumption patterns

Abstract: Scope:The aim of the presented study was to investigate the mycotoxin exposure of Ivorian population related to the consumption patterns of maize, peanuts, millet, and cassava product (attiéké).Materials and Methods:Maize flour samples (n = 51) were purchased from all Abidjan local markets, in the south of Ivory Coast, and urine (n = 99) was collected during the same reference period (July–September 2011) from volunteers living in Abidjan and Daloa cities. Reversed-phase liquid chromatography coupled with elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 33 publications
(56 reference statements)
7
35
2
3
Order By: Relevance
“…Similar data were collected in West Africa by Kouadio et al . () with 8.0 ng ml −1 DON and no DOM‐1 in human urine samples ( Turner et al , ). However, in a study among women from Shanghai from the same investigator (Turner et al , ), the data showed much lower DON levels (4.8 ng ml −1 urine and 5.9 ng mg −1 creatinine) than those in UK adults.…”
Section: Don Exposure Levels In Humans and Geographical Differencesmentioning
confidence: 92%
See 2 more Smart Citations
“…Similar data were collected in West Africa by Kouadio et al . () with 8.0 ng ml −1 DON and no DOM‐1 in human urine samples ( Turner et al , ). However, in a study among women from Shanghai from the same investigator (Turner et al , ), the data showed much lower DON levels (4.8 ng ml −1 urine and 5.9 ng mg −1 creatinine) than those in UK adults.…”
Section: Don Exposure Levels In Humans and Geographical Differencesmentioning
confidence: 92%
“…() further analysed the levels of DON in urine samples of 27 test subjects (aged 21–77 years) from Valencia (Spain) in 2010 (from September to November). These data showed a pattern similar to Kouadio's report (Rubert et al ., ; Kouadio et al ., ), in which DON was confirmed in 33.3% of the samples, and the result was much lower than the occurrence in UK populations (98.7%) (Turner et al , ). Additionally, another investigation of multiple mycotoxin exposures was also conducted using urinary biomarkers in rural subsistence farmers in Transkei, South Africa (Shephard et al , ).…”
Section: Don Exposure Levels In Humans and Geographical Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of CIT (occurrence: 12%; median: 1784 μg/kg), FB 1 (occurrence: 81%; median: 269 μg/kg), and AFB 1 (occurrence: 50%; median: 24 μg/kg) were reported in maize from Burkina Faso, whereas DON (median: 31.4 μg/kg) and ZEN (median: 13.4 μg/kg) were documented in not more than 10% of 26 samples (Warth and others ). Fifty‐one maize flour samples from Côte d'Ivoire were found to be laden with very high AFs (mean: 107.9 μg/kg) whereas FUM (mean: 355.5 μg/kg), OTA (mean: 21.5 μg/kg), and ZEN (mean: 14.0 μg/kg) levels were relatively low (Kouadio and others ). In Cameroon (Central Africa), where maize is commonly used to produce a local beer known as sha , AFs, FUM, DON, and ZEN levels in maize have been shown to reach 645, 24,225, 3,842, and 334 μg/kg, respectively (Njobeh and others ; Abia and others ; Ediage and others ).…”
Section: Short Overview On the Occurrence Of Mycotoxins In African Crmentioning
confidence: 99%
“…However, the sometimes-deadly aflatoxins released by Aspergillus sp. on contaminated maize (Kouadio et al, 2014), and the continued exposure of children to these toxins (Nduti et al, 2016) has led to proposals to return to consumption of fermented millet, in which the probiotic Yoba 2012 and GR-1 strains degrade the aflatoxins (Ahlberg et al, 2015;Mokoena et al, 2006;Musika et al unpublished;Nduti et al, 2017;Verheecke et al, 2016). For maize and other cereals, the use of microorganisms to detoxify aflatoxins has been researched, and by means of the locally made probiotic fermented food, this is expected to contribute to the reduction of a significant disease risk factor .…”
Section: Future Directionsmentioning
confidence: 99%